Optimization of Photovoltaic Performance Through the Integration of a Heatsink–Blower Cooling System Under Solar Simulator Testing Conditions - Singgih Dwi Prasetyo; Muh. Farhan Atha Farid; Tyo Febrino Fernandio Prasetyo; Nabella Sofa Nur Afiqoh; Nindia Nova Novena; Yuki Trisnoaji; Mangisi Larixon Lumban Gaol; Febrianto Sinaga; Godlisten Gladstone Kombe; Buruhan Haji Shame (Universitas Sebelas Maret, 2026)
This study examines the impact of a heatsink-based cooling system, combined with forced airflow, on the thermal and electrical performance of a photovoltaic (PV) module under controlled irradiance conditions provided by a solar simulator. The cooling configuration employed is energy-efficient and straightforward, utilizing active convection enhanced by a blower in selected trials. Two primary conditions were compared: PV without cooling and PV with different cooling configurations. The experimental results indicate that the PV + Heatsink + Blower configuration achieved the highest average electrical efficiency of 13.43%, whereas the PV Only configuration recorded the lowest, 12.45%. This difference demonstrates that temperature regulation through a combination of heatsink and assisted airflow significantly improves electrical energy conversion. Furthermore, maintaining a lower, more stable operating temperature contributes to consistent power output and reduces heat accumulation, which can accelerate performance degradation. Overall, the findings suggest that integrating a low-energy, straightforward cooling design can be an effective strategy to enhance PV performance, particularly in testing environments that use a solar simulator.